2020
DOI: 10.1002/acr.24063
|View full text |Cite
|
Sign up to set email alerts
|

Time to Lupus Low Disease Activity State in the Hopkins Lupus Cohort: Role of African American Ethnicity

Abstract: Objective. Lupus low disease activity state (LLDAS) is a potential treat-to-target goal in systemic lupus erythematosus (SLE). This study determined predictors of time to reach LLDAS in a longitudinal cohort.Methods. Patients were grouped according to LLDAS status at cohort entry. Those who did not satisfy LLDAS at cohort entry were analyzed prospectively. The Kaplan-Meier approach was used to estimate the time to LLDAS. Cox regression was used to identify patient characteristics that were associated with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(79 reference statements)
3
9
0
1
Order By: Relevance
“…Babaoglu et al found that patients with disease duration ≤1 year had shorter time to LLDAS [26]. Our study confirmed the association and further found that treatment-naïve was also a positive predictor of LLDAS achievement.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Babaoglu et al found that patients with disease duration ≤1 year had shorter time to LLDAS [26]. Our study confirmed the association and further found that treatment-naïve was also a positive predictor of LLDAS achievement.…”
supporting
confidence: 89%
“…Some previous studies found that patients with LLDAS ≥50% of follow-up time had a lower level of SLEDAI at baseline [14,22,23], and other studies found that baseline SLEDAI ≤4 was a predictor of achieving LLDAS and maintaining LLDAS for 5 years [15,26]. The present study showed that patients with lower disease activity (by PGA or SLEDAI-2K) at baseline were more quickly to achieve LLDAS.…”
supporting
confidence: 60%
See 3 more Smart Citations